PERAN GURU PAI DALAM MENGEMBANGKAN SELFCONTROL RASA EMPATI SISWA DI SDN DURI KEPA 11 KEBON JERUK JAKARTA BARAT - Karima, Litakuna; Putri Ramdhania Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of attention and emphasis on character education in schools. This study aims to describe the role and steps, as well as the supporting and inhibiting factors of Islamic Religious Education (PAI) teachers in developing selfcontrol and empathy in grade 5c students at SDN Duri Kepa 11 Kebon Jeruk Jakarta Barat. This research used a qualitative approach with a case study method. Data collection techniques included in-depth interviews with Islamic Religious Education (PAI) teachers, the principal, and students, as well as direct observation and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicate that Islamic Religious Education (PAI) teachers play an active role in developing student selfcontrol through discipline, role modeling, and strengthening the value of patience. Supporting factors in this process include a conducive school environment, clear rules, and collaboration with parents. Meanwhile, inhibiting factors include time constraints, differences in student character, and a lack of parental involvement. Nevertheless, collaboration between Islamic Religious Education (PAI) teachers, homeroom teachers, and the school supports the sustainability of student character development.